2020
DOI: 10.3390/agronomy10010147
|View full text |Cite
|
Sign up to set email alerts
|

Soil Pollution by Petroleum-Derived Substances and its Bioremediation: The Effect on Aphis fabae Scop. Infestation and Antioxidant Response in Vicia faba L.

Abstract: In this study, the effects of soil contamination with petroleum-derived substances (PDSs) (petrol, diesel fuel and used engine oil) and its bioremediation using biopreparation ZB-01 on broad bean infestation by black bean aphid Aphis fabae Scop., as well as on the antioxidant enzymes activity (superoxide dismutase (SOD), catalase (CAT) and guaiacol peroxidase (POD)) and antioxidant (non-protein thiols and proline) content in plant leaves, were determined. Results showed that after three years from the moment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…Additionally, a number of studies revealed a decrease in proline level in leaves of Plantago lanceolata [ 51 ] and Brassica juncea [ 52 ] exposed to heavy metal soil contamination. Rusin et al [ 17 ] found that soil contamination with petroleum-derived substances led to a decrease in proline content in leaves of broad bean plants. At the same time, the authors previously showed that soil contamination with diesel and gasoline led to an increase in proline content in wheat plants [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a number of studies revealed a decrease in proline level in leaves of Plantago lanceolata [ 51 ] and Brassica juncea [ 52 ] exposed to heavy metal soil contamination. Rusin et al [ 17 ] found that soil contamination with petroleum-derived substances led to a decrease in proline content in leaves of broad bean plants. At the same time, the authors previously showed that soil contamination with diesel and gasoline led to an increase in proline content in wheat plants [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that the antioxidative system and its significance for the adaptation of plants to pollution stresses has been reviewed frequently, little is known about the effects of crude oil stress on the plant antioxidative system. Some studies have shown a change in the contents of proline, non-protein thiols [ 5 , 17 ], ascorbic acid, riboflavin, anthocyanins [ 18 ], phenolic compounds, and flavonoids [ 19 ] in plants growing on oil contaminated soils. A number of authors have investigated the effect of oil pollution on the activity of plant antioxidative enzymes [ 9 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Data on changes in the level of this amino acid in plants at different concentrations of oil in the soil are quite contradictory and are determined both by the type of pollutant and the type (and even variety) of plants [ 20 ]. For example, the presence of diesel fuel and gasoline in soil has been shown to increase the accumulation of this amino acid in wheat plants, while pollution with oil products caused its decrease in the leaves of bean plants [ 63 , 64 ]. In the present experiment, the presence of oil led to a sharp increase in its content in the leaves compared to the control ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Petroleum-derived substances (PDSs) such as diesel, have become a common soil pollutant [ 1 ]. Nowadays it is considered a global problem because of the harmful effects that these compounds exert on the natural environment [ 1 ]. Contamination with PDSs can cause phytotoxicity in several plant species [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…This phytotoxicity is affected by many variables such as the time that has passed since the contamination [ 6 , 8 ], the contamination degree [ 7 , 9 ] and the plant species [ 9 , 10 ]. In addition, soil contamination with PDSs constitutes a potential danger to human health and life [ 1 ]. Therefore, efforts have been undertaken in order to find effective, economically affordable and environmentally friendly methods to restore contaminated soils [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%